Estimation of the Environment State and Ensuring Environmental Security in the Russian Arctic - E. V. Smirennikova (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
Successful development of the whole country economy requires an increase in the rate of economic growth, including through the development and processing of natural resources of the Arctic, which can lead to negative effects on the environment. The Arctic macroregion plays an important role in protective the ecological balance of the planet. The sensitivity of Arctic ecosystems increases the likelihood of regional environmental problems becoming global. Therefore, ensuring environmental safety in the Arctic should be scientifically constructed and implemented on the basis of systematic measurements of a set of indicators of the environment state. The purpose of this study is the selection, justification and analysis of indicators in accordance with the goals to preserve the environment and ensuring environmental safety of the Arctic macroregion.Five main tasks aimed at improving the state of atmospheric air, water resources, preserving biodiversity, developing and implementing environmental innovations and neutralizing production and consumption wastes were identified on the base of analysis of strategic planning documents in the sphere of environmental protection of the Russian Federation. The most fully characterizing indicators were substantiated for each task.Analysis of a dynamic series of data on the proposed indicators made it possible to identify a number of environmental features in the regions of the Russian Arctic. Among them are a high level of atmospheric air pollution; insufficient wastewater treatment and weak savings in fresh water intake by enterprises; low supply of high-quality drinking water; a high level of waste generation from industry and consumption; a small proportion of protected areas in the total area in the Russian Arctic; a low level of introduction of environmental innovations. The obtained results can be used as a basis for developing recommendations for improving the efficiency of state policy in the Arctic in the sphere of ecology.The proposed balanced system of indicators allows not only to assess the state of the environment and ensure environmental safety in the Arctic, but also to characterize the effectiveness of implementing the main objectives of environmental policy in relation to the macroregion.